2022
DOI: 10.1108/ict-05-2022-0028
|View full text |Cite
|
Sign up to set email alerts
|

Psychological empowerment and employee engagement: role of job satisfaction and religiosity in Nigeria

Abstract: Purpose This paper aims to examine the mediating role of job satisfaction in the relationship between psychological empowerment and employee engagement. There is also an investigation of the moderating effect of religiosity on psychological empowerment and job satisfaction as well as job satisfaction and employee engagement. Design/methodology/approach Data were obtained from 265 employees working in the service industry in Nigeria. The hypotheses were tested and analysed using structural equation modelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 117 publications
1
9
0
1
Order By: Relevance
“…Employee satisfaction plays a mediating role in the association between organizational learning culture and customer satisfaction (Pantouvakis and Bouranta, 2013). The intrinsic religiosity factor is a moderating variable in Nigeria in the relationship between employee engagement and employee satisfaction (Nwachukwu et al, 2022). Attendance at Six Sigma training helps to achieve job satisfaction and enhances employee morale, with employees who participated in Six Sigma training positive about their morale and job satisfaction (Cheng, 2012).…”
Section: Developing Organizational Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Employee satisfaction plays a mediating role in the association between organizational learning culture and customer satisfaction (Pantouvakis and Bouranta, 2013). The intrinsic religiosity factor is a moderating variable in Nigeria in the relationship between employee engagement and employee satisfaction (Nwachukwu et al, 2022). Attendance at Six Sigma training helps to achieve job satisfaction and enhances employee morale, with employees who participated in Six Sigma training positive about their morale and job satisfaction (Cheng, 2012).…”
Section: Developing Organizational Performancementioning
confidence: 99%
“…Employee satisfaction plays a mediating role in the association between organizational learning culture and customer satisfaction (Pantouvakis and Bouranta, 2013). The intrinsic religiosity factor is a moderating variable in Nigeria in the relationship between employee engagement and employee satisfaction (Nwachukwu et al. , 2022).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Consistent with findings, most studies on psychological empowerment have shown that the construct has a positive effect on job performance (Varma and Malhotra, 2022; Ambad et al , 2021; Tripathi et al , 2020; Singh and Singh, 2018). According to Nwachukwu et al (2022), there is a mediating role of job satisfaction in the relationship between psychological empowerment and employee engagement. The division of authority that managers provide their employees stems from empowerment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ini diklasifikasikan berdasarkan moral yang sangat baik, hubungan emosional, dan produktivitas profesional di tempat kerja dan administrasi (Shaheen et al, 2022). (Nwachukwu et al, 2022) Kesejahteraan emosional dan mental karyawan distimulasi, dan mereka terinspirasi untuk melakukan pekerjaan terbaik mereka, ketika kondisi yang tepat tercipta.…”
Section: Employee Engagementunclassified